Intrafamilial phenotypic variability in four families with Anderson‐Fabry disease. (20th September 2013) - Rigoldi, M.; Concolino, D.; Morrone, A.; Pieruzzi, F.; Ravaglia, R.; Furlan, F.; Santus, F.; Strisciuglio, P.; Torti, G.; Parini, R.
<x xml:space="preserve">Abstract</x> We analysed the clinical history of 16 hemizygous males affected by Anderson‐Fabry Disease, from four families, to verify their intrafamilial phenotypic variability. Seven male patients, ranging from 26 to 61 years of age, died, whereas nine (age range 23–55) are alive. Eleven patients have undergone enzyme replacement therapy (ERT) for a period of 5–10 years. We have found a wide range of intrafamilial phenotypic variability in these families, both in terms of target‐organs and severity of the disease. Overall, our findings confirm previous data from the literature showing a high degree of intrafamilial phenotypic variability in patients carrying the same mutation. Furthermore, our results underscore the difficulty in giving accurate prognostic information to patients during genetic counselling, both in terms of rate of disease progression and involvement of different organs, when such prognosis is solely based on the patient's family history.